Sex differences in time trends in acute coronary syndrome management and in 12-month lethality: Data from the French MONICA registries. (15th August 2022) - Gauthier, Victoria; Montaye, Michèle; Ferrières, Jean; Kai, Samantha Huo Yung; Biasch, Katia; Moitry, Marie; Amouyel, Philippe; Dallongeville, Jean; Meirhaeghe, Aline
Abstract: Background: Sex differences in clinical presentation, patient care and fatal outcomes after an acute coronary syndrome (ACS) have been reported. However, recent improvements in the care and treatment of ACSs have not been assessed with regard to possible sex differences. Aim: To assess sex differences in trends between 2006 and 2016 in the characteristics of ACSs, their management, and the associated mortality. Methods: We assessed all men and women (aged 35–74) covered by the MONICA registries in north, east and south-west France and having been hospitalized for an incident (first) ACS during a 12-month period in 2006 or a 6-month period in 2016. We analyzed the patients' clinical, biochemical, electrocardiographic and care-related data, and their vital status 28 days and 12 months after the ACS. Results: In 2006, women were older (<0.0001) and had more atypical symptoms than men ( p < 0.01). These differences were no longer statistically significant in 2016. Medical care improved in both men and women. However, revascularization treatment, prescriptions of platelet aggregation inhibitors, statins, and functional rehabilitation were still more frequently provided to men than to women ( p < 0.01) in 2016, independently of confounders. The 28-day or 12-month case fatality was not different between men and women in both 2006 and 2016. Conclusions: The results of the present study evidenced an improvement over time in the management of ACS. However, although there were no longer sex differences in the patients' age and clinical presentation, women with ACS were still less likely than men to receive revascularization and pharmacological treatments in 2016. Highlights: Medical care improved in both men and women over a 10 year period Women with ACS were still less likely than men to receive revascularization and pharmacological treatments in 2016 The 28-day or 12-month case fatality was not different between men and women